Evaluation of Root Canal Cleaning and Irrigant Penetration Using Different Irrigation Protocols: A Combined SEM and Single‐Tooth Micro‐CT Study - Alfredo Iandolo; Niccolò Giuseppe Armogida; Davide Mancino; Gianrico Spagnuolo; Mariangela Cernera; Dina Abdellatif (Clinical and Experimental Dental Research)
ABSTRACT Objectives This study evaluated the effectiveness of different irrigation techniques in removing debris and smear layers and in improving irrigant penetration within root canals. Particular attention was given to the 3D Cleaning technique, which combines ultrasonic activation with internal heating of sodium hypochlorite. Material and Methods Fifty‐one single‐rooted human mandibular premolars were used. Group A (n = 50) was divided into five subgroups (n = 10 each), each receiving a different irrigation protocol (control, syringe irrigation, sonic activation, ultrasonic activation, and 3D Cleaning). Scanning electron microscopy (SEM) at ×1000 magnification was used to evaluate debris and smear layer removal based on a validated scoring system. Group B (n = 1) consisted of a single premolar with a lateral canal in the apical third, examined using microcomputed tomography (micro‐CT). The same tooth underwent all five irrigation protocols in sequence, with radiopaque irrigant penetration evaluated after each and confirmed through sequential micro‐CT scans. A power analysis confirmed the adequacy of sample size (n = 50; α = 0.05, power = 80%). Non‐parametric tests were used, including Kruskal–Wallis ANOVA for intergroup comparisons, followed by Mann–Whitney U tests with Bonferroni correction for post hoc pairwise analysis (p < 0.05 considered significant). Results The 3D Cleaning technique (ultrasonic activation + internal heating) achieved the lowest debris and smear layer scores and the highest irrigant penetration depth (~0.6 mm) into the lateral canal. The control group showed no penetration and the highest debris scores. Conventional syringe and sonic activation showed moderate cleaning and penetration (0.2–0.3 mm), while ultrasonic activation alone showed slightly better results (~0.4 mm). Conclusion The 3D Cleaning technique demonstrated superior effectiveness in root canal cleaning and irrigant penetration compared to conventional irrigation methods. These results support the clinical relevance of heating‐activated irrigation protocols to enhance root canal disinfection.